Evaluation and diagnostic of concrete elements localized in marino environment of the Ite district, Tacna - Laguna Chite, Milagros Natali (2020)
In the Tacna region, buildings close to the sea often present pathologies in the concrete elements. These pathologies over time generate the development of the deterioration of the same concrete affecting the durability and service life of the buildings. The research aims to provide technical expertise in the stages of the start, planning and execution of buildings considering the vulnerability linked to a marine environment; by evaluating the mechanical, physical and chemical properties of concrete, diagnosing pathologies and concluding with a repair proposal. The research site corresponds to the Municipal Recreation Complex "Los Humedales de Ite", considering that it is exposed to a marine environment and a distance to the sea less than 2 km. Preliminary and detailed inspection was used for the development of research. Preliminary inspection identified exposure conditions (weather characteristics), and detailed inspection determined concrete properties through laboratory testing. The results were evaluated by considering the standards of the ACI, NTP, ASTM and ASOCRETO standards; it is concluded that the quality of the concrete is poor for a severe marine atmosphere because the transport of harmful agents occurs through the porosity and absorption of the concrete. The physicochemical characteristics of the materials indicated that the contaminated ingredient is the fine aggregate due to its high chloride index, a factor that adds up to the corrosion process of the reinforcing steel.